2016
DOI: 10.1111/jan.13172
|View full text |Cite
|
Sign up to set email alerts
|

Gender and socio‐economic inequalities in health and living conditions among co‐resident informal caregivers: a nationwide survey in Spain

Abstract: The study highlights gender and socio-economic inequalities in informal caregiving and its negative consequences. These findings may be useful in the design of policies and support programmes targeting the most affected groups of informal caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 47 publications
(93 reference statements)
2
23
1
2
Order By: Relevance
“…Comparing 19 European countries, Sweden had the highest degree of availability of formal care [21]. Outside of Europe, formal support is even more scarce [22]. Availability of formal care has been shown to mitigate effects of stressors and improve wellbeing in caregivers [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing 19 European countries, Sweden had the highest degree of availability of formal care [21]. Outside of Europe, formal support is even more scarce [22]. Availability of formal care has been shown to mitigate effects of stressors and improve wellbeing in caregivers [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Female sex is a risk factor not only for becoming a caregiver but also for experiencing caregiving as a burden [ 3 , 22 ]. High caregiver burden is in turn linked with poor caregiver health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions of family caregivers in the hospital and at home are not the same, and it is necessary to explore if the stressors work in the same way in the two settings. In this study, we focus on anxiety as it is one of the lesser studied negative emotional consequences and it has a high impact and importance [22]. The systematic reviews by Loh et al [19] and Sallim et al [20] reported a prevalence of anxiety of 21.4% in caregivers of relatives who have suffered a stroke [19], and 43.6% in caregivers of relatives who suffer from dementia [20].…”
Section: Introductionmentioning
confidence: 99%
“…There is an overabundance of cross-sectional and longitudinal studies on the impact of family care on the health of caregivers worldwide [ 13 , 14 ]. In Spain, there have been also cross-sectional [ 7 , 15 , 16 , 17 ] and longitudinal studies that have tried to evaluate the association between family care and the impact on health [ 18 , 19 ] but there is no cohort of caregivers that has been followed for more than 12 months and with follow-up periodicities at reasonable intervals.…”
Section: Introductionmentioning
confidence: 99%